UNDERSTANDING EFFECTS OF STATE INITIATIVES ON EDUCATIONAL INCLUSION: AN INDIAN PERSPECTIVE - Gourish Chandra Mondal,; Palash Majumder, (International Journal of Psychosocial Rehabilitation, 2020)
There is some section of children with developmental disabilities encountering learning disabilities. It means the performance of the child is found to be lower than the expected performance of a particular class level. Some conditions may be easily detected where as others need closer observation and detailed assessment in order to diagnose the condition variously The study investigates the problems of students with disabilities in the process of education and the state initiatives to provide basic amenities to Persons with disabilities to make them part of community. The study reveals that most of the families of children with special needs are living with low annual income irrespective of their caste. There is a big difference between the abilities claimed by parents than they are actually living with. Most of the children with special needs have problems in speaking, writing, mobility, bathing, clothing, and managing themselves in the toilet. This intensity necessitates the inculcation of taking care of special needs and giving support. The children with special needs have interest in playing kids but because of their low cognitive growth and parental restrictions, some of them are playing with younger age children than them and some are staying back at home without playing.